Analisis Pengaruh Inflasi dan Kurs Rupiah Terhadap Neraca Perdagangan di Jawa Barat (Tahun 2013-2022) - Habibi, Syamsul Allim Syah (CV. ITTC INDONESIA, 2022)
With the occurrence of the Covid-19 pandemic, export-import activities have experienced a significant decline in every trade balance around the world. This study aims to determine the effect of the inflation rate and the rupiah exchange rate against the US dollar on the value of the trade balance in West Java province with a vulnerable period from 2013 to 2022. The method used in this study is multiple linear regression analysis which looks at how the influence of from one independent variable to the dependent variable, the data used is secondary data originating from the Central Bureau of Statistics (BPS). The results of the study suggest that the inflation rate has no significant effect while the exchange rate has a positive and significant effect on the trade balance